EVALUATION OF EFFICACY OF OOSHAKADI LEKHANA BASTI IN HYPERLIPIDAEMIA - A SINGLE BLINDED RANDOMIZED CONTROLLED STUDY - Sreelakshmi, Chaganti; Kumari, R. Shylaja; V. Sanpeti, Rajashekhar; Dasari, Srilakshmi (International Journal of Ayurveda and Pharma Research, 2015)
Disorders of lipid metabolism and obesity are reported by 30% to 40% with increased prevalence. These conditions are co-related with Medo-pradoshajavikara - a condition leading for excess formation of Meda (lipids) directly from Amarasa Dhatu (improperly formed chyle) and travel all over body through blood circulation. This stage is compared to hyperlipidaemia where it is defined as excess circulation of lipids in blood. The present study highlights the efficacy of Ooshakadi Lekhana Basti (type of therapeutic enema) processed by Ooshakadigana Dravyas (alkaline substances). Ooshaka (alkaline sand) was special drug and used almost for first time which is synonymously known as Kshara Mrittika. A single blinded controlled study has been conducted on 45 patients randomized in to three groups each containing 15 patients. The control drug was atrovastin. Average mean reduction of lipids were found statistically significant (p<0.05) in the experimental groups over control group in all types of lipids except HDL which has presented increase pattern. Hence the study establishes the efficacy of Ooshakadi Lekhana Basti in hyperlipidaemia of obese and non-obese patients.